An overview on the effectiveness of the human trafficking law in Malaysia / Nur Atiqah Fatma Hamdan, Nurul Hidayah Sulaiman and Nurul Nadia Ghazali - Hamdan, Nur Atiqah Fatma; Sulaiman, Nurul Hidayah; Ghazali, Nurul Nadia (2011)
The researchers want to do an overview on the effectiveness of anti-trafficking of human law available in Malaysia. The researchers intended to highlight the problems that arise after the enactment of the Anti-Trafficking in Persons Act 2007 which later was amended to become the Anti-Trafficking and Anti Smuggling of Migrants Act 2007 (Amendment 2010). In addition, the researchers also made comparison to other countries in respect of the prosecution of antihuman trafficking law. The comparison of the legislation in the area of human trafficking with other countries has uncovered the loopholes in our legal system and the researchers have obtained better prospective on the issue from it. The researchers applied qualitative techniques in their research. Firstly, they had conducted library-based research from books, report and journal articles. The information extracted from these sources is used as reference in order to give an overview on the issue in interest. The second method used is semi-structured interview whereby the researchers are learning on different opinions and perspective on the issue when the respondents answered the interview questions. The objective of the interview is to gain a better understanding on the current issue of human trafficking law in Malaysia. The last method used is through comparative study with other countries such as Austria and Australia since the respective countries are considered as having the best system related to human trafficking law. Through this research, the researchers have gained a lot of knowledge particularly on the on issue of human trafficking and get to know the minimum standard of law that should be applied by the state as required by the international treaties on human trafficking. In conclusion, the researchers have found that Malaysia's position in the execution of human trafficking law to be below the required standard and need to be improved.